68Ga-PSMA-11 PET/CT in prostate cancer local recurrence: impact of early images and parametric analysis - Sachpekidis, Christos; Pan, Leyun; Hadaschik, Boris; Kopka, Klaus; Haberkorn, Uwe; Dimitrakopoulou-Strauss, Antonia (American journal of nuclear medicine and molecular imaging, 2018)
68Ga-PSMA-11 PET/CT performed 60 min post tracer injection (p.i.) can underestimate prostate cancer (PC) local recurrence, due to high 68Ga-PSMA-11 urinary bladder accumulation. Aim of this analysis is to evaluate the complementary role of early dynamic and parametric PET imaging in patients with PC local recurrence. Sixteen patients with PC biochemical relapse attributed to local recurrence underwent dynamic 68Ga-PSMA-11 PET/CT scanning of the pelvis and whole-body PET/CT. Data analysis was based on visual analysis of the PET/CT scans, SUV calculations, quantitative analysis based on two-tissue compartment and Patlak models as well as parametric imaging based on Patlak analysis. 12/16 patients were PSMA-positive in the static 68Ga-PSMA-11 PET/CT scans (60 min p.i.). All 12 lesions corresponding to PC local recurrence were detected in the early dynamic images at a median time of 4.5 min p.i. (range = 1.5-11.5 min). Moreover, early dynamic PET imaging could detect local recurrence in 1/4 static PET/CT-negative patients. Tracer accumulation in the urinary bladder began at a median time of 10 min (range = 6.0-17.5 min). All PC local recurrences visible on late static PET/CT and the local recurrence, which was positive only in early dynamic but not in late PET images, could be delineated on Patlak images. The present findings indicate that early dynamic 68Ga-PSMA-11 PET/CT scan of the pelvis up to 12 min p.i. as well as Patlak analysis, performed in addition to the conventional PET/CT acquired at 60 min p.i., seem a practical approach to increase the detection rate of PC local recurrence.
Im Titel ist "68" in 68Ga-PSMA-11 PET/CT hochgestellt
Gesehen am 10.05.2019